Quality of Education According to the Assessment of University’s Key Partners - Zh. A. Ermakova; Yu. N. Nikulina (Высшее образование в России)
The article addresses the problems of the quality of education in general, including from the perspective of employers. The authors believe that the mechanism for assessing the quality of education should be implemented through the active participation of the University’s key partners and employers in the educational process.The article presents the results of a study of the level of satisfaction with the quality of education of graduates estimated by enterprises that are the key partners of Orenburg State University (2020). The first set of questions involved an analysis of the degree of participation of employer organizations in the educational process and assessment of the level of training of university graduates. The second block included an assessment of personnel needs and demands on graduates when applying for a job, as well as an analysis of the prospects for developing forms of cooperation between employers in the region and the University.In conclusion, we offer a list of recommendations for improving the effectiveness of internal independent assessment of the quality of education with the involvement of representatives of employers. The list includes recommendations aimed at enhancing their participation in improving the system of training for the region’s economy.